A Analisis Kompensasi Kerja, Motivasi Kerja dan Lingkungan Kerja Islami Yang Mempengaruhi Kinerja Dosen dan Karyawan ITB AAS Indonesia - Sri Laksmi Pardanawati; Romdhoni, Abdul Haris (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the effect of compensation, motivation, and Islamic work environment on the performance of Teachers and Employees at ITB AAS Indonesia. The analysis used is multiple regression analysis and uses data sourced from respondents. This type of research uses quantitative research with the data used is primary data and uses the questionnaire method in data collection. Based on the results of the analysis, it is known that compensation has a significant effect on employee performance from variable testing, it was found that H0 was rejected and Ha was accepted with a significant value of 0.001. Motivation has a significant effect on employee performance, from testing variables, it was found that H0 was rejected and Ha was accepted with a significant value of 0.039. The Islamic work environment has a significant effect on employee performance, employees from variable testing found that H0 was accepted and Ha was rejected with a significant value of 0.000.